(untitled) (INNOVATIVE ECONOMY, 2020)
Shulskyi M.G., Shulskyi A.M. DEVELOPMENT OF COOPERATIVE MOVEMENT TECHNOLOGY IN THE LEGACY OF HRYHORII HALAHAN Purpose. The purpose of the article is to consider the development of technology of the cooperative movement, which is based on teachings of Hryhorii Halahan. Methodology of research. General scientific and special methods are used to study the problems: dialectical, deductive, inductive, abstraction, concretization and comparative method. The following research methods are used: dialectical method of cognition – when considering the historical path of H. Halahan’s activity; theoretical generalization and comparison – for the development of the conceptual apparatus and research on the development of cooperative movement technology; abstract and logical – in the theoretical generalization of the essence and achievements of the scientific heritage of H. Halahan. The primary sources in the study are historical Ukrainian works. Findings. A study of the main milestones in the life and work of a prominent figure in Ukraine in the second half of the nineteenth century Hryhoriy Halahan is conducted. The main emphasis in the research processes is focused on: consideration of the conditions for the development of various spheres of social relations in the middle of the XIX century in Ukraine; development and implementation of technology of H. Halahan’s cooperative activity; determining the impact of the technology of H. Halahan’s cooperative activity on the development of agricultural relations. A review of the life of Hryhoriy Halahan, as a prominent figure in Ukrainian economic thought, is implemented. Originality. The generalization of H. Halahan’s versatile activity is carried out; in particular the technologies of cooperative activity are singled out. Practical value. Assessing the practical steps of implementation of the technology of H. Halahan’s cooperative activity gives grounds to assert the need for further research on the enrichment of science in this direction. The obtained results of the study are aimed at highlighting the “white spots” of the history of the technology of cooperative movement in the Ukrainian lands of the XIX century. Key words: Hryhorii Halahan, public relations, cooperation, technologies of cooperative activity, savings and loan cooperation, credits, cooperative activity.